Peningkatan Pemahaman dan Motivasi Siswa melalui Strategi dan Media Pembelajaran PAI Berbasis Audio Visual di Sekolah Dasar - Hermawan, Ganjar (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This research is motivated by the challenges in improving the understanding and motivation of third-grade elementary school students in performing prayer practices as part of Islamic Religious Education (PAI) learning. The objective of this study is to evaluate the effectiveness of using audio-visual-based learning media in addressing these challenges. This study employs a qualitative descriptive method with a case study design conducted at SDN Sindangraja 1 Cianjur. Data were collected through participatory observation and in-depth interviews with teachers and students, and analyzed using thematic analysis techniques. The findings reveal that the use of audio-visual media significantly enhances students' understanding of prayer material, active participation in the learning process, and motivation to correctly perform prayer practices. The implications of this research suggest that integrating audio-visual media in PAI learning can be an effective strategy to improve the quality of religious education at the elementary school level. This research also opens opportunities for further development related to innovations in PAI teaching methods that can be widely implemented.